2009
DOI: 10.5194/bg-6-3131-2009
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of iron and temperature on Antarctic phytoplankton and microzooplankton assemblages

Abstract: Abstract. Iron availability and temperature are important limiting factors for the biota in many areas of the world ocean, and both have been predicted to change in future climate scenarios. However, the impacts of combined changes in these two key factors on microbial trophic dynamics and nutrient cycling are unknown. We examined the relative effects of iron addition (+1 nM) and increased temperature (+4 • C) on plankton assemblages of the Ross Sea, Antarctica, a region characterized by annual algal blooms an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 88 publications
4
84
0
Order By: Relevance
“…Our findings imply that if, due to climate change, present habitats for larval krill overwintering and nursery in the South Scotia Ridge and southern Scotia Sea 1 become ice free in winter, there may be an increase in food for larval krill development and growth [32][33][34][35][36][37] . If, however, the seasonal sea-ice cover does not extend as far north in future, then larvae that are released from under the sea ice in spring will be farther south in the Weddell Sea (south of the South Scotia Ridge in spring) and will take longer to reach the Scotia Sea 17 ( Supplementary Fig.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 76%
“…Our findings imply that if, due to climate change, present habitats for larval krill overwintering and nursery in the South Scotia Ridge and southern Scotia Sea 1 become ice free in winter, there may be an increase in food for larval krill development and growth [32][33][34][35][36][37] . If, however, the seasonal sea-ice cover does not extend as far north in future, then larvae that are released from under the sea ice in spring will be farther south in the Weddell Sea (south of the South Scotia Ridge in spring) and will take longer to reach the Scotia Sea 17 ( Supplementary Fig.…”
Section: Nature Ecology and Evolutionmentioning
confidence: 76%
“…Studies of Antarctic phytoplankton indicate that a rise in temperature alone causes only a modest increase in their growth rate (e.g. Rose et al, 2009;Boyd et al, 2013Boyd et al, , 2015 and this increase is often overcompensated by the negative effects of increased temperature on abiotic and biotic stressors such as nutrient limitation and grazing (Caron and Hutchins, 2013;Lewandowska et al, 2014).…”
Section: Climate-driven Changes To the Southern Oceanmentioning
confidence: 99%
“…In general, Chl a concentrations were low (1-2 µg L-1) in spite of high dissolved inorganic nutrients concentrations (Cascaes et al, 2012), as commonly reported in Admiralty Bay (Lipski, 1987;Lange et al, 2007;Kopczynska, 2008). One of the explanations for this paradox is usually associated to the low micronutrient iron availability, which is considered as one of the main factors limiting phytoplankton growth under high macronutrients conditions (Martin et al, 1991;Rose et al, 2009). Studies developed on Antarctic phytoplankton cultures showed that both iron addition and increase in water temperature, lead to rise of chlorophyll biomass (Rose et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…One of the explanations for this paradox is usually associated to the low micronutrient iron availability, which is considered as one of the main factors limiting phytoplankton growth under high macronutrients conditions (Martin et al, 1991;Rose et al, 2009). Studies developed on Antarctic phytoplankton cultures showed that both iron addition and increase in water temperature, lead to rise of chlorophyll biomass (Rose et al, 2009). In this way, the increase of biomass in LS was mainly conditioned by rise of temperature, which melts the ice providing the micronutrient iron to phytoplankton growth (Martin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation